2013
DOI: 10.26719/2013.19.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of dietary counselling on the improvement of end-stage renal disease patients

Abstract: Proper nutrition may help to reverse the wasting syndrome in dialysis patients with kidney disease on dialysis. This intervention study aimed to identify malnutrition problems and assess the effect of dietary counselling on improvement of health status of end-stage renal disease patients subjected to haemodialysis. Pre-intervention data were collected from 41 patients attending El Haram dialysis centre, Giza, Egypt; 97.5% of the patients were considered mildly to moderately malnourished and multiple malnutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 15 publications
(21 reference statements)
2
21
0
Order By: Relevance
“…Medical nutrition therapy provided by dieticians for haemodialysis patients have been shown to improve patients' Karnofsky performance scale scores, quality of life, dietary intake, nutritional status and nutritional knowledge . In our study, more than half of the study population were found to have some degree of malnutrition, yet not all of them (43%) were referred to dietician for medical nutrition therapy.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Medical nutrition therapy provided by dieticians for haemodialysis patients have been shown to improve patients' Karnofsky performance scale scores, quality of life, dietary intake, nutritional status and nutritional knowledge . In our study, more than half of the study population were found to have some degree of malnutrition, yet not all of them (43%) were referred to dietician for medical nutrition therapy.…”
Section: Discussionmentioning
confidence: 59%
“…To date, there are no studies on the nutritional status of hospitalized patients requiring haemodialysis support in our local population. Literature revealed the prevalence of malnutrition in patients on haemodialysis (based on SGA tool) ranging from 23% to 76% in various countries . The objective of this study is to utilize the SGA tool to assess the nutritional status of hospitalized patients requiring haemodialysis.…”
mentioning
confidence: 99%
“…In-depth Review Fleck et al [53] , 2007 Discussion Carver et al [57] , 1995 Review Blinkhorn [61] , 2012 Review O'Connor et al [64] , 2012 Review Catania et al [65] , 2013 Report Quantitative Study design Questionnaire used Mapes et al [8] Longitudinal KDQOLSF-36 Kao et al [13] , 2009 Cross sectional SF-36 Abraham et al [14] , 2008 Case control, follow up WHOQOL-BREF Kimmel et al [15] , 2008 Prospective Satisfaction with Life Scale (SLS), McGill QOL, Single item Patel et al [16] , 2002 Prospective McGill QOL, Beck Depression Griva et al [17] , 2009 Cross sectional SF-36 Elder et al [19] , 2008 Cross sectional, case mix KDQOLSF-36 Sanner et al [20] , 2002 Cross sectional SF-36, Nottingham Health Profile Tondra [22] , 2014 Conceptual Framework, CS Quality of Life Index Dialysis, Mingardi et al [23] , 1999 Prospective SF-36 Seica et al [24] , 2009 Cross sectional SF-36, KDQOLSF-36 Bakewell et al [25] , 2002 Longitudinal /intervention KDQOLSF-36 Theofilou [26] , 2012 Cross sectional/ Observational WHOQOL-BREF, GHQ-28 Kim et al [28] , 2013 Cross sectional KDQOLSF-36 White et al [29] , 2002 Retrospective cohort SF-36 Painter et al [32] , 2000 Experimental/Intervention SF-36 Ouzouni et al [33] , 2009 RCT SF-36, Quality of Life Index Agakhani et al [34] , 2012 Case control/comparative SF-36 Hegazy et al [35] , 2013…”
Section: Resultsmentioning
confidence: 99%
“…[22,25] , influence of dialysis care practice [27] , self-efficacy, treatment satisfaction [28] , pre-dialysis clinic attendance [29] , exercise [30] . Intervention such as dietary counseling [34,35] , individual/group counselling [14,36,37,40] , education on regular exercise [31][32][33] , physical and psychological rehabilitation interventions, palliative care to manage symptoms [38] , and cognitive behavior therapy to reduce depression [39] Inverse association of factors with QOL More worries and higher depression [13] , ignorance about the basic facts of one's disease [14] , Pain, financial constraints [14] , psychological and spiritual factors [15] , emotional impact, physical impact on daily living, role of religious and spiritual beliefs [16] , beliefs related to illness and treatment [17] , anxiety, depression, suicidal ideation, grief of loss of kidney, self-image selfesteem [18] , sleep quality [19] , sleep related breathing disorders [20] , as well as erectile dysfunction, patient satisfaction with care, depressive aspects, symptom burden, and perception of intrusiveness of illness [21] , female gender [22][23][24]26] , ethnicity [25] , older age [26] , less education [24,26] , poor nutritional status [25] and divorced marital status, Illness and treatment beliefs [17] , work and Symptom domain [25] No or very weak association of fa...…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nurse-led educational interventions for hemodialysis patients in China and in Australia demonstrated success in improving the dietary practices of these patients (Shi et al, 2013;Sandlin et al, 2013). Additionally, a study ESRD patients undergoing dialysis in Giza, Egypt demonstrated a significant improvement in their nutritional knowledge following nutritional counselling sessions (Hegazy et al, 2013).…”
Section: Discussionmentioning
confidence: 99%